Insertion of moderate character through project learning in Islamic Religious Education courses - Yulianti; Nurul Murtadho; Yusuf Hanafi (Indonesian Journal of Islamic Religious Education, 2023)
Teachers play an essential role in managing learning in the classroom, developing moral values, positive attitudes, and social skills, and training responsible individuals with moderate character. Research related to religious moderation is starting to be widely carried out. This research aims to find out how heterogeneous the research is regarding project-based learning in Islamic Religious Education (PAI) courses to strengthen the moderate character of prospective teachers. This research uses the systematic literature review (SLR) method in Scopus-indexed journals. Based on a quantitative descriptive approach, a search engine was used to search the PRISM protocol through four stages: identification, screening, feasibility, and suitability (inclusion). The research results showed that 500 articles were identified using the word moderate through the SefoRA.com application. At the screening stage, the remaining 200 articles obtained had duplicate status, did not match the fields, and the data used was not appropriately valid. At the feasibility stage, 40 articles were obtained after the elimination process, and 11 articles discussed keywords character strengthening and met the inclusion criteria, which were included in the analysis via the VosViewer engine.